Ethical aspects of dark ecology and their importance in modern society (Journal of Philosophy Culture and Political Science, 2025)
The article is devoted to the study of the ethicalaspects of darkecology, aconceptproposed by BritishphilosopherTimothyMorton.Darkecology is consideredas an integralpart of the philosophy of ecology,offeringnewethicalprinciples of interaction between manandnaturein the era of the Anthropocene.Thearticleanalyzes the basicprinciples of darkecology,suchas the rejectionofanthropocentrismand the recognition of the value of allforms of life,whichinvolverethinking the place of manin the worldand the formation of a newenvironmentalresponsibility.Thearticleexamines the potential of darkecologytocreate a moreharmoniousrelationshipwithnature,aswell as the ethicalconsequences of itsadoption.Specialattention is paid to the concept of "hyperobjects"–globalenvironmentalphenomenathatdemonstrate the interconnectedness of alllivingbeings.Therelevance of furtherresearch on the ethicalaspects of darkecologyfor the formation of a moresustainableandequitablefuture is emphasized.Keywords: dark ecology, Timothy Morton, anthropocentrism, ethics, environmental responsibility, hyperobjects, sustainable development.